Systemic lupus erythematosus: novel aspects of pathogenesis and treatment 1 - Putterman, Chaim; Schwartz, Noa (Henry Stewart Talks, 2019)
Overview of innate and adaptive immunity, Specific effectors of innate immunity in SLE, Specific effectors of adaptive immunity in SLE